The effect of perceived stress and psychological well-being on mompreneurs - Hardiansari, Afiyanti; Kadiyono, Anissa Lestari; Sulistyobudhi, Rezki Ashriyana (INSPIRA: Indonesian Journal of Psychological Research, 2024)
In recent years, the rise of mompreneurs has become a notable phenomenon, as more mothers engage in managing small businesses while simultaneously fulfilling family responsibilities. Mompreneur refer to a mother figure who owns and works on small business, also known as Micro, Small, and Medium Entreprises or MSME. While balancing dual roles as business owners and caregivers, they often face significant challenges in maintaining their businesses and attending to household and family responsibilities. These challenges can lead to daily life struggles perceived as stress, which, in turn, may impact their psychological well-being. This study aims to examine whether perceived stress affects the psychological well-being of mompreneurs. Using a quantitative approach, the study targeted mompreneurs in Bandung City and employed convenience sampling, resulting in 102 respondents. Measuring tools will be using Perceived Stress Scale (PSS) consists of 10 items and Psychological Well-Being Scale consists of 42 items while demographic factors suh as age, educational background, sales turnover, and marital status were also included. The result showed that there is an effect of perceived stress on psychological well-being from regression analysis (p < 0,05) with an r squared of 0.156. These findings highlight the importance of addressing stress management and promoting psychological well-being among mothers managing MSMEs to ensure they can effectively fulfill their dual roles and maintain a healthy balance.